Community-Based Gerontic Nursing and Quality of Life Among Older Adults - Mustain, Mustain (Oshada, 2026)
Population aging presents significant challenges to healthcare systems, particularly in maintaining the quality of life among older adults living with chronic conditions and functional limitations. Community-based gerontological nursing has emerged as a strategic approach to support healthy aging and promote independence. This study aimed to analyze the impact of structured community-based gerontological nursing interventions on the quality of life among older adults. A quasi-experimental pretest–posttest control group design was employed involving 80 participants aged 60 years and above. The intervention group received a twelve-week structured program including comprehensive geriatric assessment, individualized care planning, ADL support, chronic disease monitoring, psychosocial counseling, and family engagement, while the control group received usual care. Data were collected using validated instruments measuring multidimensional quality of life, functional status (ADL), and depressive symptoms. Statistical analysis revealed significant improvements in quality of life (p < 0.001), functional independence (p < 0.001), and reduced depressive symptoms (p < 0.001) in the intervention group compared to the control group. The findings indicate that community-based gerontological nursing significantly enhances holistic well-being among older adults and supports sustainable aging-in-place strategies.